A MODIFIED CONJUGATE GRADIENT METHOD WITH GLOBAL-CONVERGENCE FOR UNCONSTRIANED OPTIMIZATION PROBEMS - ABDULRAHMAN, ASMAA M.; FATHI, BAYDA G. (Journal of Duhok University, 2021)
In this paper a new conjugate gradient method for unconstrained optimization is suggested, the new method is based on Conjugate Descent (CD) formula which is a modified of the CD formula and which is also sufficiently descent and globally convergent. Numerical evidence shows that this new conjugate gradient algorithm is considered as one of the competitive conjugate gradient methods.